Communicative Religious Leadership in Aquaculture Communities: An Exploration of Social, Spiritual, and Financial Dimensions in Guiding Fish Farmers - M. Anis Bachtiar; Aun Falestien Faletehan; Muhammad Haidarsyah Kasyafillah; Amera J. Masoud; Achmad Murtafi Haris (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2025)
This study explores the role of local religious leaders in Koi fish farming communities in Blitar, Indonesia, focusing on how they influence social structures, convey spiritual values, and support the community’s financial well-being through communicative leadership practices. Using a qualitative grounded theory approach, data were collected through in-depth interviews with 20 participants across four aquaculture communities. The findings reveal that religious leaders strengthen social cohesion, mediate conflicts, and promote ethical behavior by employing interpersonal, symbolic, and ritual communication. Religious values, such as honesty, perseverance, hard work, and environmental care, are actively communicated through daily interactions. Additionally, these leaders provide training, economic guidance, and moral motivation that help fish farmers align material success with spiritual responsibility. This study highlights that communication serves as a central mechanism in religious leadership, fostering a value-based and sustainable aquaculture community. The findings contribute to the development of religious social capital theory, planned behavior theory, and religious leadership in the context of local economic communities.